Investigation of Material Properties by Means of Magnetic Methods - Rasek, Józef Jan; Stoklosa, Zbigniew (Engineering Transactions, 2006)
In the present paper, magnetic method of determination of ferrite content in austenite steels, based on saturation polarisation and magnetic polarisation of ferrite near the remanence point, have been presented for Fe-Cr-Ni-type alloys. Magnetic phase analysis, taking into account the distribution of total magnetic losses on eddy current losses, relaxation losses and hysteresis losses, have been discussed for low-carbon and low-alloy steels. The formulas on tangent angle of eddy current, hysteresis and relaxation (additional) losses have been presented. General formulas for magnetic permeability and coercive force have also been presented in terms of internal magnetic and material parameters. These parameters allowed to analyse the structural changes in magnetic materials. Examples of the influence of chemical composition, structural defects and thermal annealing on the changes of saturation polarisation, magnetic permeability, coercive force, magnetic hysteresis and relaxation losses have been discussed for low-carbon steels and amorphous alloys.